OSchol: an online consensus survival web server for cholangiocarcinoma prognosis analysis. Issue 4 (April 2021) - Wang, Qiang; An, Yang; Wang, Fengling; Zhang, Guosen; Zhang, Lu; Dong, Huan; Xin, Junfang; Li, Yongqiang; Ji, Shaoping; Guo, Xiangqian
Abstract: Background: As the most common biliary ducts, cholangiocarcinoma (CHOL) is an aggressive malignancy with complex pathological context, high mortality and relapse rate. The current therapy of CHOL is mainly performed with surgery followed by chemoradiotherapy. Due to the high metastasis and relapse rate of CHOL, the prognosis of CHOL is still poor, and the molecular prognostic system is to be constructed. Methods: In this study, we have established an online prognostic analysis web server named OSchol to evaluate the correlation between candidate genes and survival for CHOL. Results: The prognostic values of previous published biomarkers in OSchol, including ITIH4, PTEN and DACH1, have been validated by OSchol. In addition, we have identified novel potential prognostic biomarker for CHOL using OSchol, that E2F1 has significant prognostic ability in OSchol (both TCGA and GSE107943 cohorts). Conclusion: Our study provides a platform for researchers and clinicians to screen, develop and validate their genes of interest to be potential prognostic biomarkers for CHOL and may also help guide the targeted therapies for CHOL.